Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1128/jvi.72.5.3837-3844.1998
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Mapping of Transcripts in Herpesvirus 6 Variants

Abstract: To define the molecular features characteristic of the early stages of infection of lymphocytes with human herpesvirus 6 (HHV-6) variant A or B, we studied the temporal regulation of expression of selected sets of viral genes. Thus, U42, U94, U89-U90, U73, and U39 are α genes since their transcripts (i) were made in the presence of inhibitors of protein synthesis and (ii) were detected 3 h after infection of untreated cells. U41, U53, U31, and U19 are β genes since their expression is inhibited by cycloheximid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(58 citation statements)
references
References 40 publications
2
54
0
1
Order By: Relevance
“…In 1995, a study by Challoner et al (13) found HHV-6 in the oligodendrocytes of MS patients but not controls and found a higher concentration of infected cells in areas of demyelination compared to unaffected white matter; it was the first time that HHV-6 was related to MS. Since then, a variety of studies have investigated the possible role of HHV-6 in MS with contradictory results between those which support the possible involvement of HHV-6 in MS pathogenesis (1-5, 14, 17, 19, 21, 37, 38, 42, 44, 46), and those which refute that association (31,32,41); this controversy may be interpreted in the context of the different laboratory techniques (DNA extraction, PCR method, amount of template in the reaction), different groups of MS patients, different control populations, and different study designs (transversal, longitudinal).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1995, a study by Challoner et al (13) found HHV-6 in the oligodendrocytes of MS patients but not controls and found a higher concentration of infected cells in areas of demyelination compared to unaffected white matter; it was the first time that HHV-6 was related to MS. Since then, a variety of studies have investigated the possible role of HHV-6 in MS with contradictory results between those which support the possible involvement of HHV-6 in MS pathogenesis (1-5, 14, 17, 19, 21, 37, 38, 42, 44, 46), and those which refute that association (31,32,41); this controversy may be interpreted in the context of the different laboratory techniques (DNA extraction, PCR method, amount of template in the reaction), different groups of MS patients, different control populations, and different study designs (transversal, longitudinal).…”
Section: Discussionmentioning
confidence: 99%
“…The primers and probes derived from previously published data (18,45) and were designed using Primer Express Software (Applied Biosystems). As it has been previously described (32), the presence of U94 transcripts in absence of expression of the other HHV-6 genes was considered HHV-6 latent infection. Meanwhile, the expression of more than one HHV-6 gene was considered active viral infection.…”
Section: Hhv-6 Quantitative Real-time Pcr For Cdnamentioning
confidence: 99%
“…The results are shown in Figure 1. Transcripts of U91, U42 (immediate-early genes) [Mirandola et al, 1998] and U22, a late gene [French et al, 1999], were present at all time points. All samples were negative when amplified without previous retrotranscription (data not shown).…”
Section: Hhv-6 Infection Of Endothelial Cellsmentioning
confidence: 94%
“…It was demonstrated that U90 gene transcript was produced under immediate early conditions and was detected soon after viral infection (3 hr) [Mirandola et al, 1998]. Moreover, as a sufficient level of transcript was detected not only in infected cells but also in patients' peripheral blood mononuclear cells (PBMCs) [Yoshikawa et al, 2003], it is speculated that the U90 gene product may be detected in infected cells or PBMCs collected from ES patients.…”
Section: Introductionmentioning
confidence: 99%